2018
DOI: 10.1161/jaha.117.008125
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Use in Acute Myocardial Infarction: Insights From the National Cardiovascular Data Registry

Abstract: BackgroundTicagrelor is a P2Y12 receptor inhibitor with superior clinical efficacy compared with clopidogrel. However, it is associated with reduced efficacy when combined with a high‐dose aspirin.Methods and ResultsPatients in the acute coronary treatment and intervention outcomes network (ACTION) Registry‐Get With The Guidelines (GWTG) with acute myocardial infarction from October 2013 through December 2014 were included in the study (167 455 patients; 622 sites). We evaluated temporal trends in the prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…21,22 Recently, national registries of ACS in the USA and European countries have demonstrated an increasing use of the potent P2Y12 inhibitors and their efficacy in clinical practice. [23][24][25][26] However, the benefits of potent P2Y12 inhibitors in the Asian population have not been clarified. The multicenter, double-blind, randomized PHILO trial compared the efficacy and safety of ticagrelor vs. clopidogrel in 801 patients with ACS in East Asian countries including Japan.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Recently, national registries of ACS in the USA and European countries have demonstrated an increasing use of the potent P2Y12 inhibitors and their efficacy in clinical practice. [23][24][25][26] However, the benefits of potent P2Y12 inhibitors in the Asian population have not been clarified. The multicenter, double-blind, randomized PHILO trial compared the efficacy and safety of ticagrelor vs. clopidogrel in 801 patients with ACS in East Asian countries including Japan.…”
Section: Discussionmentioning
confidence: 99%
“…After data collection was complete, the balance of covariates between intervention and usual care groups was assessed using standardized differences. 19 Data on patient race were collected because prior studies suggested that patients of nonwhite race were less likely to be prescribed higherpotency P2Y 12 inhibitors 6 and that racial differences in medication nonadherence likely mediate disparities in cardiovascular morbidity and mortality 20 ; race was retrospectively abstracted from the medical record.…”
Section: Primary Analysesmentioning
confidence: 99%
“…We believe that this is unlikely to have significantly affected outcomes. Fourth, in the study by Sanchez‐Ramos et al, the standard arm had a higher use of clopidogrel (93%) compared to trends in P2Y12 inhibitor use in contemporary U.S. practices 3,4 . However, sensitivity analysis after excluding this study still showed similar results.…”
Section: Discussionmentioning
confidence: 62%
“…The standard components of DAPT include aspirin as well as a P2Y12 receptor inhibitor 1,2 . Clopidogrel, which remains the most commonly used P2Y12 inhibitor, is an irreversible platelet aggregation inhibitor of P2Y12 receptors, and requires hepatic conversion to an active metabolite via the cytochrome P450 enzymatic pathway 3‐6 . Due to genetic variation in the general population, which results in the loss of function of CYP2C19 genes, approximately 30% of the U.S. population have an inadequate antiplatelet response to clopidogrel, and are therefore at a potential risk for thrombotic complications (particularly stent thrombosis) 7‐9 .…”
Section: Introductionmentioning
confidence: 99%